2016
DOI: 10.1155/2016/1508752
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antihypertensive Medications in Iranian Patients

Abstract: Introduction. Appropriate adherence to medication is still a challenging issue for hypertensive patients. We determined adherence to antihypertensive(s) and its associated factors among 280 Iranian patients. Methods. They were recruited consecutively from private and university health centers and pharmacies in four cities. The validated Persian version of the 8-item Morisky Medication Adherence Scale (MMAS-8) was administered to measure adherence. Results. Mean (±SD) overall MMAS-8 score was 5.75 (±1.88). Abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
(31 reference statements)
5
25
1
1
Order By: Relevance
“…For statistical analysis purpose, high and medium level of treatment adherence was together termed as good adherence level, whereas low adherence was termed as poor adherence level. [18,22] RESULTS Table 1 revealed that high level of treatment adherence was found among only 22 (12.9%) study participants as per the MMAS, whereas medium and low level of adherence was observed in 59 (34.7%) and 89 (52.4%) participants, respectively. It was also reported that more than half of the female study participants, 43 (55.8%) had low level of treatment adherence.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For statistical analysis purpose, high and medium level of treatment adherence was together termed as good adherence level, whereas low adherence was termed as poor adherence level. [18,22] RESULTS Table 1 revealed that high level of treatment adherence was found among only 22 (12.9%) study participants as per the MMAS, whereas medium and low level of adherence was observed in 59 (34.7%) and 89 (52.4%) participants, respectively. It was also reported that more than half of the female study participants, 43 (55.8%) had low level of treatment adherence.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were obtained in a study done in Iran as well as in India. [22,28] Some of the studies did not find any such association. [18,23] In this study, patients indulging in regular physical activity and those practising salt-restricted diet had good compliance to therapy while alcohol and tobacco usage had no effect on adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, "non-adherence" encompasses the diverse factors for patients not following a treatment recommendation. [9,12,17] 2. METHOD 2.1 Design An exploratory descriptive research design was used to achieve the purpose of the study.…”
Section: Definitions Of Termsmentioning
confidence: 99%
“…Persian version of the MMAS-8 to be valid and reliable tool with an overall Cronbach's α coefficient of 0.697 and test-retest reliability showed good reproducibility (r = 0.940). [9] (3) The third tool was related to factors affecting drug adherence checklist as reported by WHO (2003) which include five main dimensions: (a) Social and Economic Dimension …”
Section: Toolsmentioning
confidence: 99%
See 1 more Smart Citation